The effect of TOMM40 on spatial navigation in amnestic mild cognitive impairment - Laczó, Jan; Andel, Ross; Vyhnalek, Martin; Matoska, Vaclav; Kaplan, Vojtech; Nedelska, Zuzana; Lerch, Ondrej; Gazova, Ivana; Moffat, Scott D; Hort, Jakub (Neurobiology of aging, 2015)
The very long (VL) poly-T variant at rs10524523 ("523") of the TOMM40 gene may hasten the onset of late-onset Alzheimer's disease (LOAD) and induce more profound cognitive impairment compared with the short (S) poly-T variant. We examined the influence of TOMM40 "523" polymorphism on spatial navigation and its brain structural correlates. Participants were apolipoprotein E (APOE) ε3/ε3 homozygotes with amnestic mild cognitive impairment (aMCI). The homozygotes were chosen because APOE ε3/ε3 variant is considered "neutral" with respect to LOAD risk. The participants were stratified according to poly-T length polymorphisms at "523" into homozygous for S (S/S; n = 16), homozygous for VL (VL/VL; n = 15) TOMM40 poly-T variant, and heterozygous (S/VL; n = 28) groups. Neuropsychological examination and testing in real-space human analog of the Morris Water Maze were administered. Both self-centered (egocentric) and world-centered (allocentric) spatial navigation was assessed. Brain magnetic resonance imaging scans were analyzed using FreeSurfer software. The S/S group, although similar to S/VL and VL/VL groups in demographic and neuropsychological profiles, performed better on allocentric navigation (p ≤ 0.004) and allocentric delayed recall (p ≤ 0.014), but not on egocentric navigation. Both S/VL and VL/VL groups had thinner right entorhinal cortex (p ≤ 0.043) than the S/S group, whereas only the VL/VL group had thinner left entorhinal cortex (p = 0.043) and left posterior cingulate cortex (p = 0.024) than the S/S group. In conclusion, TOMM40 "523" VL variants are related to impairment in allocentric spatial navigation and reduced cortical thickness of specific brain regions among aMCI individuals with (LOAD neutral) APOE ε3/ε3 genotype. This may reflect a specific role of TOMM40 "523" in the pathogenesis of LOAD.
Keywords: membránové transportní proteiny; Alzheimerova nemoc; Cognitive Dysfunction; Magnetic resonance imaging; Magnetic Resonance Imaging; homozygot; Apolipoprotein E3; mozková kůra; senioři; Cerebral Cortex; Aged; Male; lidé; kognitivní dysfunkce; Genotype; lidé středního věku; Humans; Homozygote; mitochondriální importní komplex; riziko; Mitochondrial Precursor Protein Import Complex Proteins; Middle Aged; Neuropsychology; Membrane Transport Proteins; Polymorphism, Genetic; neuropsychologické testy; Hippocampus; Morris Water Maze; Alzheimer’s disease; Spatial Navigation; senioři nad 80 let; Aged, 80 and over; prostorová navigace; mužské pohlaví; polymorfismus genetický; Memory; Apolipoprotein E; ženské pohlaví; genotyp; Neuropsychological Tests; Alzheimer Disease; Female; apolipoprotein E3; magnetická rezonanční tomografie; Risk